Scientific Documentation: Traditional Ink Recipes and Writing Materials used in Manuscripts in the Malay Region - Mohd Roslin Hazer, Nurul Amira; Abdul Razak, Rajabi; Othman, Raihan; Md. Zain, Dzul Haimi; Awang, Arita Hanim; Baniyamin, Nurhaya; Musa, Muktaruddin (UKM Press, 2021)
There is a scarcity of documentation and descriptions of such an indigenous ink formula in the literature. Even the rare records of this priceless heritage only mention the ink’s constituents. The legacy of Malay indigenous ink manufacturing should be preserved in historical archives due to a lack of knowledge about the proportions of each ingredient and the techniques involved. All information and knowledge about ink manufacturing is thought to be passed down orally rather than through written documents from one generation to the next. Even worse, knowledge of ink production is restricted to a selected group of people, including palace officials, religious teachers and their students. As a result, this project focuses on finding the history of Malay traditional ink using a variety of methods, including examining existing early Malay manuscripts, conducting structured interviews and analysing literature sources on ink recipes from throughout the world. Traditional Malay manuscript ink is made from natural sources such as coal, black coal from extracted mangosteen skin, cashew gum from the bark of the cashew tree, glutinous rice, egg white, oil from the rind of a cashew, black pepper, salt, virgin coconut oil and palm vinegar, and other ingredients found in the area. Handmade paper is imported from European and Southeast Asian countries. This is a new programme aimed at learning more about the history of Malay traditional ink and expanding indigenous knowledge of Malay technology and other materials used in the production of Malay manuscripts. The empirically demonstrated legacy of black ink illustrates the wisdom of the traditional Malay community, even though the Malays are able to understand the chemical composition included in any materials used to manufacture the traditional ink despite their lack of formal education.